Electrophysiological evidence for adult age-related sparing and decrements in emotion perception and attention - Pollock, Joshua W.; Khoja, Nadia; Kaut, Kevin P.; Lien, Mei-Ching; Allen, Philip (Frontiers in Integrative Neuroscience, 2012)
The present study examined adult age differences in processing emotional faces using a psychological refractory period (PRP) paradigm. We used both behavioral and event-related potential (P1 component) measures. Task 1 was tone discrimination (fuzzy vs. pure tones) and Task 2 was emotional facial discrimination (“happy” vs. “angry” faces). The stimulus onset asynchrony (SOA) between the two tasks was 100 ms, 300 ms, and 900 ms. Earlier research observed age deficits in emotional facial discrimination for negative (angry) than for positive (happy) faces (Baena et al., 2010). Thus, we predicted that older adults would show decreased attentional efficiency in carrying out dual-task processing on the P1 (a component linked to amygdalar modulation of visual perception; Rotshtein et al., 2010). Both younger and older groups showed significantly higher P1 amplitudes at 100- and 300-ms SOAs than at the 900-ms SOA, and this suggests that both age groups could process Task 2 emotions without central attention. Also, younger adults showed significantly higher P1 activations for angry than for happy faces, but older adults showed no difference. These results are consistent with the idea that younger adults exhibited amygdalar modulation of visual perception, but that older adults did not.